Potassium tert-Butoxide Facilitated Amination of Carboxylic Acids with N,N-Dimethylformamide - Huang, Yuanjing; Zhang, Jing (Synthesis, 2022)
Herein a practical and efficient potassium tert-butoxide (KOtBu)-facilitated amination of carboxylic acids with N,N-dimethylamine is described. In the presence of catalytic amount of KOtBu, a variety of aliphatic and aromatic carboxylic acids are transformed to N,N-dimethylamides using DMF as the dimethylamine reagent with the assistance of trimethylacetic anhydride. The applicability of this protocol is demonstrated by late-stage dimethylamidation of complex drug molecules. A plausible reaction mechanism involving KOtBu-facilitated in situ amine generation from formamide decomposition and anhydride-mediated condensation is proposed on the basis of mechanistic investigations.
Keywords: amidation; N,N-dimethylformamide; carboxylic acid; potassium tert-butoxide